1985
DOI: 10.1259/0007-1285-58-685-41
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation by flow cytofluorometry of response of tumours of the uterine cervix to radiotherapy

Abstract: We are presently involved in a project to investigate the use of flow cytofluorometry in assessing, by means of serial biopsies, the response to radiotherapy of tumours of the uterine cervix. This technique enables changes in the DNA content profiles and content of proliferating cells in the tumour biopsies to be determined at intervals as therapy progresses. A means has been devised to quantitate the content of hyperdiploid cells, hypertetraploid cells, and dead and dying cells, by computer analysis of DNA vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…It was found that 36 tumours (72%) would have been correctly assigned on the basis of any one sample whereas 14 tumours (28%) could have been incorrectly designated since one of the samples fell into a different ploidy group from the others. If the tumours were further subdivided into three subgroups (<10%, 10-30%, >30% of Cell death Previous studies have confirmed the validity of using ethidium bromide staining to determine the level fo cell death in vivo and in vitro (Dyson et al, 1984a(Dyson et al, , 1984b(Dyson et al, , 1984c. The range of values found in the various tumours (8-92%) was the greatest of any of the areas quantitated ( Figure 4).…”
Section: \mentioning
confidence: 71%
See 2 more Smart Citations
“…It was found that 36 tumours (72%) would have been correctly assigned on the basis of any one sample whereas 14 tumours (28%) could have been incorrectly designated since one of the samples fell into a different ploidy group from the others. If the tumours were further subdivided into three subgroups (<10%, 10-30%, >30% of Cell death Previous studies have confirmed the validity of using ethidium bromide staining to determine the level fo cell death in vivo and in vitro (Dyson et al, 1984a(Dyson et al, , 1984b(Dyson et al, , 1984c. The range of values found in the various tumours (8-92%) was the greatest of any of the areas quantitated ( Figure 4).…”
Section: \mentioning
confidence: 71%
“…Cells were again collected by centrifugation and resuspended in 2-4 ml of PBS (50%) and HBSS (50%); an equal volume of the same medium was then added containing 15,uM acridine orange (AO) and the sample was placed in the flow cytometer and the sample flow started and allowed to equilibriate. Figure 2 and were modified from our previous studies (Dyson et al, 1984a(Dyson et al, , 1984b(Dyson et al, , 1984c to allow for the wider range of DNA content seen in these tumours. Table IV.…”
Section: \mentioning
confidence: 99%
See 1 more Smart Citation
“…The cervix tumour cell lines employed in this study were established in primary culture from cervix biopsy tissue taken routinely during radiotherapy at Cookridge Hospital (Dyson et al, 1984a). Six cell lines were used: 754, 612, 995, 090, 329, 708.…”
Section: Cell Culturementioning
confidence: 99%
“…The cervix tumour cell lines employed in this study were established in primary culture from cervix biopsy tissue taken routinely during radiotherapy at Cookridge Hospital (Dyson et al, 1984a). Six cell lines were used: 754, 612, 995, 090, 329, 708. These were maintained as monolayer cultures from which multicellular aggregates were obtained as required by using the method of Sutherland and Durand (1976).…”
Section: Cell Culturementioning
confidence: 99%